1985
DOI: 10.1021/bi00342a021
|View full text |Cite
|
Sign up to set email alerts
|

Olefin oxygenation and N-dealkylation by dopamine .beta.-monooxygenase: catalysis and mechanism-based inhibition

Abstract: In an initial communication [May, S. W., Mueller, P. W., Padgette, S. R., Herman, H. H., & Phillips, R. S. (1983) Biochem. Biophys. Res. Commun. 110, 161-168], we reported that 1-phenyl-1-(aminomethyl)ethene hydrochloride (PAME) is an olefinic substrate for dopamine beta-monooxygenase (DBM; EC 1.14.17.1) which inactivates the enzyme in an apparent mechanism-based manner. The present study further characterizes this reaction. The inactivation reaction yields kinact = 0.23 min-1 at pH 5.0 and 37 degrees C and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 43 publications
5
63
0
Order By: Relevance
“…We previously reported that 3Ј-and 4Ј-OHAPP derivatives are not taken into resealed chromaffin granule ghosts at a detectable rate (Padgette et al, 1985;Perera et al, 2003). However, as 4Ј-halo APP derivatives are significantly more hydrophobic and are freely taken up by SH-SY5Y and other cells; we expected that these derivatives may also be taken up into chromaffin granule ghosts through simple diffusion.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously reported that 3Ј-and 4Ј-OHAPP derivatives are not taken into resealed chromaffin granule ghosts at a detectable rate (Padgette et al, 1985;Perera et al, 2003). However, as 4Ј-halo APP derivatives are significantly more hydrophobic and are freely taken up by SH-SY5Y and other cells; we expected that these derivatives may also be taken up into chromaffin granule ghosts through simple diffusion.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, data in Table 1 show that 4Ј-halogen substitution increases the VMAT inhibition potency from -F to -I, parallel to their overall hydrophobicities. Previous studies have shown that APP derivatives possess potent irreversible inhibition properties toward MAO (McDonald et al, 1985) and D␤M (Padgette et al, 1985). The structural similarities, gradually increasing VMAT inhibition potencies and hydrophobicities within the series of 4Ј-halogen substitutes APP derivatives make them a unique series of probes that can be used to examine the effects of the perturbation of DA metabolism in catecholaminergic neurons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations